Motivational Interviewing in Psychotic Disorders - Barkhof, Emile; Haan, Lieuwe d.; Meijer, Carin J.; Fouwels, Annemarie J.; Keet, Ireneus P.M.; Hulstijn, Kai P.; Schippers, Gerard M.; Linszen, Don H. (Current Psychiatry Reviews, 2006)
Patients with schizophrenia and related disorders often present problematic behaviour, such as non-adherence to medication or substance abuse, which have a negative influence on the course of the disease. Changes in such maladaptive behaviour are often difficult to accomplish in this group of patients because of specific disease related symptoms such as active psychotic symptoms, negative symptoms and cognitive disturbances. Over the last ten years, treatment strategies incorporating forms of Motivational Interviewing have been tried to influence these problems in a positive direction. Motivational Interviewing is an intervention which has proved to be successful in altering behaviour in the field of substance abuse disorders and also shows promising results in other health care areas. With the emphasis on a non-judgemental and empathetic attitude, patients are engaged in strategically directed conversations about their problems in which ambivalences on behaviour change are explored and patients are helped to move through different stages of change. This article provides a narrative review of the research data on the application of Motivational Interviewing in patients with schizophrenia and related disorders.
Keywords: behaviour change